Electrocatalytic Evaluation of a Horseradish Peroxidase Biosensor Based on a Novel Bi-Ag Bimetallic Nanocomposite. (2017) - van der Horst, Charlton; Silwana, Bongiwe; Iwuoha, Emmanuel; Somerset, Vernon
Abstract: The present work illustrates the construction and application of bismuth-silver bimetallic nanoparticles (Bi-AgNPs) in biosensor construction for the detection of peroxide (H2 O2 ). The biosensor was constructed by drop-casting of horseradish peroxidase onto the Bi-AgNPs/GCE sensor. Impedance analysis revealed that the R ct value for the bare GCE obtained was 2.548 × 10 3 Ω and increased to 5.768 × 10 3 Ω for the HRP/Bi-AgNPs/GCE biosensor. This increased value of R ct indicated hindrance to the electron transfer, providing evidence for the immobilization of insulating HRP on the Bi-AgNPs/GCE surface. The HRP/Bi-AgNPs/GCE biosensor was successfully applied for sensitive detection of H2 O2 by differential pulse voltammetry. Well defined peaks were observed with a low linearity range from 0.02 × 10 −6 to 1.0 × 10 −6 M ( R 2 = 0.991), with a limit of detection of 0.06 μM. The results obtained for the HRP/Bi-AgNPs/GCE biosensor compared well within the range of similar biosensors reported.